Pengaruh Upah Minimum Provinsi, PDRB, IPM, Dan Tingkat Pengangguran Terhadap Penyerapan Tenaga Kerja di Pulau Sumatra - Nissya Kaniaputri Jayadiwinata; Ruth Eviana Hutabarat (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
Indonesia's economic development is a complex process that includes improving people's welfare, productivity and expanding employment opportunities. However, regional disparities are still evident, especially in several provinces on the island of Sumatra. There is a phenomenon of minimum wage increases without an increase in labor absorption (high wage low employment growth) and economic growth without job creation (jobless growth), resulting in an imbalance between economic growth and labor absorption, which slows down the rate of decline in the unemployment rate. This study aims to analyze the effect of UMP, PDRB, IPM, and unemployment rate on labor absorption in ten provinces in Sumatra during 2020-2024. The data was obtained from  Badan Pusat Statistik (BPS) and analyzed using panel data regression with the Fixed Effect Model (FEM) method. The results of the analysis show that the UMP has a negative and significant effect on labor absorption, while the GRDP, HDI, and unemployment rate have a positive and significant effect on labor absorption in Sumatra in 2020–2024.